PROBLEMATIKA PENERAPAN KURIKULUM 2013 DI SD YPMM TEBINGTINGGI DAN STRATEGI DALAM MENGATASINYA - Kasiono . (Jurnal Ilmiah Dikdaya, 2017)
Abstract: The purposeof thisstudywas to determine problems facedby SDYPMM (Yayasan Pendidikan Mayang Mangurai) Tebing Tinggi, District of Tanjung Jabung Barat, Jambi Province In2013’sCurriculum (K-13)Implementation andanalyzes trategiesu sedto over comethese problems. This research is aqualitati vedescriptive study. Techniques usedin sampling was purposive sampling.Based on the researchfounda number ofthe problems, among others: the teacheris stilldifficult tochange the old mindset; in practicethe majorityof teachersare still experiencing difficulties inimplementing the K-13both in terms ofpreparation, implementation, andfinalization oflearning outcomes, particularlyin terms ofthe evaluation; interms ofthe availability ofmeans of learning, teaching materialsbookis stillverylimited; while the parents of the student sat the beginningis still wides pread confusionin addressingthe K-13.While based on theSWOT analys is found strategie sto over comethe seproblems, namely(a) Optimizingthe key components ofthe quality ofteaching and learning inelement ary school YPMMTebingting gi for the implementation ofK-13in coll aboration with parents andt he community (Strategy SO). (b) Performa variety of training that supports the implementation ofK-13to teachers and printa soft copy ofthe text book K-13 of the Go vernment to include the participation of parents and communities(WO strategies). (c) Take advantage ofallthe resources that existin SDYPMMT ebingting gi to implement K-13in the limitationsof the Governmentin setting upfacilities / infrastructurethat support the successful implementation ofK-13(Strategy ST). And(d). To the quality of teaching and facilities / infras tructure independent ly bySDYPMMT ebingtinggiin the limitationsofthe Governmentin setting upfacilities / infrastructur et hat support the successfulimplementation ofK-13(Strategy WT). Keywords: Implementation, K-13 (Curriculum 2013), Problems, Strategy